The ultimate Stallone reader : Sylvester Stallone as star, icon, auteur - Holmlund, Chris (Wallflower Press, 2014)
Sylvester Stallone has been a defining part of American film for nearly four decades. He has made an impact on world entertainment in a surprisingly diverse range of capacities? as actor, writer, producer, and director? all while maintaining a monolithic presence. With The Ultimate Stallone Reader, this icon finally receives concerted academic attention. Eleven original essays by internationally-known scholars examine Stallone's contributions to mainstream cinema, independent film, and television. This volume also offers innovative approaches to star, gender, and celebrity studies, perf.